NATIONALITY IN BRAZILIAN LAW - Rodrigue, Paulo Cesar Villela Souto Lopes; Gbedemah, Stephen Edem (PANORAMA OF BRAZILIAN LAW, 2018)
This paper aims to present the rules of nationality in brazilian law. Therefore, it will demonstrate the constitutional cases of how nationality can be acquired and lost; and the possible distinctions between birth and naturalized nationals in the brazilian law.